IDENTIFIKASI POTENSI PASAR PRODUK OLAHAN PINDANG WILAYAH PAMOYANAN BOGOR - Ferdisar Adrian (MAGMA : JURNAL MAGISTER MANAJEMEN, 2013)
Fishing is one of the economic sectors that have the potential and important role for the Indonesian economy. Fisheries development is an integral part of national development. The aim of this research is to describe the general overview of steamed fish business and to identify the potential market for processed products steamed fish in Sub Pamoyanan, South Bogor subdistrict. The method used in this research is a case study with the case unit is processing industry engaged in fishing in the Village Pamoyanan, South Bogor. The aim is to give a detailed description of the background, characteristics and characters clear from the case or the status of the individual, which then of distinctive properties above will be a matter of a general nature. The subject of this research may be individuals, groups, institutions or society.By looking at some of the above conditions, market opportunities steamed fish are still open, both to meet domestic needs as well as to penetrate the global market. Fish as part of the staple diet in everyday life will certainly have continuity request. Besides the public taste and awareness of the importance of consuming fish is also an important factor on the demand of fish, including steamed fish. Based on the information obtained, pemindangan fish in Sub Pamoyanan also been marketed to the supermarket, which means customers are low-income segments of the population to high (all classes). It is also associated with the production of boiled fish whose quality consists of several levels, ranging from low to high quality. one type of fish that is durable because it has been preserved through steamed fish. The potential steamed market processed fish products is still very open to any entrepreneur boiled fish, this is due to the increasing needs of the community. The potential market could be scattered in several areas of the city of Bogor. Open market potential must be observed by businesses in the Pamoyanan Village as an opportunities and strategies that efforts must be made so that the opportunities of the potential market can be maximized by good.Keywords : potential market, steamed fish